Efficacy and safety of adult human bone marrow-derived, cultured, pooled, allogeneic mesenchymal stromal cells (Stempeucel®): preclinical and clinical trial in osteoarthritis of the knee joint. Issue 1 (December 2016) - Gupta, Pawan; Chullikana, Anoop; Rengasamy, Mathiyazhagan; Shetty, Naresh; Pandey, Vivek; Agarwal, Vikas; Wagh, Shrikant; Vellotare, Prasanth; Damodaran, Devi; Viswanathan, Pachaiyappan; Thej, Charan; Balasubramanian, Sudha; et al.
Abstract Background Osteoarthritis (OA) is a common and debilitating chronic degenerative disease of the joints. Currently, cell-based therapy is being explored to address the repair of damaged articular cartilage in the knee joint. Methods The in vitro differentiation potential of adult human bone marrow-derived, cultured, pooled, allogeneic mesenchymal stromal cells (Stempeucel®) was determined by differentiating the cells toward the chondrogenic lineage and quantifying sulfated glycosaminoglycan (sGAG). The mono-iodoacetate (MIA)-induced preclinical model of OA has been used to demonstrate pain reduction and cartilage formation. In the clinical study, 60 OA patients were randomized to receive different doses of cells (25, 50, 75, or 150 million cells) or placebo. Stempeucel® was administered by intra-articular (IA) injection into the knee joint, followed by 2 ml hyaluronic acid (20 mg). Subjective evaluations—visual analog scale (VAS) for pain, intermittent and constant osteoarthritis pain (ICOAP), and Western Ontario and McMaster Universities Osteoarthritis (WOMAC-OA) index—were performed at baseline and at 1, 3, 6, and 12 months of follow-up. Magnetic resonance imaging of the knee was performed at baseline, and at 6 and 12 months follow-up for cartilage evaluation. Results Stempeucel® differentiated into the chondrogenic lineage in vitro with downregulation of Sox9 and upregulation of Col2A genes. Furthermore, Stempeucel® differentiated into chondrocytes and synthesized a significant amount of sGAG (30 ± 1.8 μg/μg GAG/DNA). In the preclinical model of OA, Stempeucel® reduced pain significantly and also repaired damaged articular cartilage in rats. In the clinical study, IA administration of Stempeucel® was safe, and a trend towards improvement was seen in the 25-million-cell dose group in all subjective parameters (VAS, ICOAP, andWOMAC-OA scores), although this was not statistically significant when compared to placebo. Adverse events were predominant in the higher dose groups (50, 75, and 150 million cells). Knee pain and swelling were the most common adverse events. The whole-organ magnetic resonance imaging score of the knee did not reveal any difference from baseline and the placebo group. Conclusion Intra-articular administration of Stempeucel® is safe. A twenty-five-million-cell dose may be the most effective among the doses tested for pain reduction. Clinical studies with a larger patient population are required to demonstrate a robust therapeutic efficacy of Stempeucel® in OA. Trial registration Clinicaltrials.govNCT01453738 . Registered 13 October 2011.